Incidence of postdural puncture headache: Two different fine gauge spinal needles of the same diameter - Ruslan Abdullayev; Omer Burak Kucukebe; Bulent Celik; Sinan Hatipoglu; Filiz Hatipoglu (Wolters Kluwer Medknow Publications, 2014)
Objective: The aim of this study was to compare two spinal needles with different bevel designs regarding their technical handling capacities and complication rates. Materials and Methods: After the clinical trials Ethics Committee approval and informed consents from the patients, 220 pregnant female patients undergoing elective cesarean delivery under spinal anesthesia were recruited in the study. Patients were divided into two groups as, Group A (n = 110) and Group Q (n = 110); who received spinal anesthesia via 26 gauge (26-G) atraumatic spinal needle (Atraucan® , B. Braun Melsunger, Germany) and via 26-G Quincke spinal needle (Spinocan® , B. Braun Melsunger, Germany), respectively. Procedure duration, puncture attempts and postdural puncture headache (PDPH) incidence were recorded. The costs of the spinal needles were also noted. Results: There were no significant differences between the two groups in spinal puncture attempts and procedure durations. Similarly, incidence, severity, onset time and duration of headache were not found to be significantly different between the two groups. Ten patients (9.2%) in Group A and 11 (10.3%) in Group Q had developed PDPH. Conclusion: Both spinal needles offer good handling characteristics with comparable incidence of PDPH. Taking into account economical factors 26-G Quincke needle may be preferred to 26-G Atraucan® .